1997
DOI: 10.1021/es9600946
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Desorption of Organic Contaminants from Long-Term Contaminated Soil Using Distributed Mass Transfer Rates

Abstract: Simulation models for the fate and transport of groundwater contaminants are important tools for testing our understanding of transport phenomena at long-term contaminated sites and for designing remedial action plans. A finite difference formulation for contaminant transport including a distribution of contaminant mass-transfer rates between the water and soil is developed. Optimal model simulations using both log-normal and γ distributions of mass transfer rates are compared to the two-site equilibrium/ kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
144
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(147 citation statements)
references
References 32 publications
(56 reference statements)
3
144
0
Order By: Relevance
“…This model was updated recently by replacing the linear sorption isotherm (K d ) with uranyl surface complexation reactions (Liu, Zachara et al 2008) and accounting for changes in pH, and calcium and carbonate concentrations in solution by adding multi-rate ion exchange reactions (Liu, Shi et al 2009). Culver, Hallisey et al (1997) found that the fraction of initial mass of organic contaminants remaining on contaminated sediment versus time indicated an increase in resistance to desorption with time. The authors found that a compartmentalized model representing soil mass fractions with different mass transfer rates taken from a lognormal or gamma distribution fit tailing behavior in column experiments more accurately than a one or two-site model, which assumes that mass transfer rates do not vary.…”
Section: Component Additivity Methodologymentioning
confidence: 98%
See 1 more Smart Citation
“…This model was updated recently by replacing the linear sorption isotherm (K d ) with uranyl surface complexation reactions (Liu, Zachara et al 2008) and accounting for changes in pH, and calcium and carbonate concentrations in solution by adding multi-rate ion exchange reactions (Liu, Shi et al 2009). Culver, Hallisey et al (1997) found that the fraction of initial mass of organic contaminants remaining on contaminated sediment versus time indicated an increase in resistance to desorption with time. The authors found that a compartmentalized model representing soil mass fractions with different mass transfer rates taken from a lognormal or gamma distribution fit tailing behavior in column experiments more accurately than a one or two-site model, which assumes that mass transfer rates do not vary.…”
Section: Component Additivity Methodologymentioning
confidence: 98%
“…The authors tried to fit Br data with a physical non-equilibrium model (2 domain or dual porosity model) and the results indicated that all water was mobile and that physical nonequilibrium played no significant role in Br transport. A one-dimensional distributed rate coefficient model (Culver, Hallisey et al 1997) was used fit the U column data. Mass transfer coefficients were obtained from a gamma distribution and a single value of K d was assumed for all sorption sites.…”
Section: Component Additivity Methodologymentioning
confidence: 99%
“…Several complex factors affect the phenomenon of transfer and dispersion of air pollutants around us. Temporal climate patterns in an area (weather conditions) and the geographic area under study affect how the emissions are transferred and dispersed (22)(23)(24)(25). On a cross-local scale, airflow or lack of airflow are two main factors that have an impact on the transition and dispersion process of pollutants (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…All but one of these models requires at least two (mathematical) compartments to fit the experimental data. These compartments can then define a combination of an instantaneous compartment where no mass transfer limitation is assumed with a dynamic compartment where mass transfer is limited (Ball and Roberts 1991;Sabbah et al 2005), two dynamic compartments (Brusseau et al 1991;Weber et al 1992;Xing and Pignatello 1996;Cornelissen et al 1998;Ghosh et al 2000;Shor et al 2003;Gamst et al 2004) or a continuum of compartments with various parameters (Culver et al 1997;Werth et al 2000;Werth and Hansen 2002). Although sometimes excellent fits of experimental and modeled data were demonstrated in the different papers, the physical explanation of the desorption process and its limitations is only briefly elaborated and do not include the effect of particle-size distribution.…”
Section: Introductionmentioning
confidence: 99%